Treatment results in patients with lymphoblastic lymphoma treated at the Centre of Oncology, Krakow Division - Cybulska-Stopa, Bożena; Rolski, Janusz; Ziobro, Marek; Hetnał, Marcin (Contemporary Oncology/Współczesna Onkologia, 2010)
Between 1980 and 2000, 30 patients with lymphoblastic lymphoma were treated at the Medical Oncology Clinic of the Centre of Oncology (Krakow Division). At first the APO and Coleman’s treatment protocols were used. In 1993, in order to improve treatment results, a modification of Coleman’s regimen was introduced, i.e. the dose of doxorubicin was intensified. In the original Coleman’s regimen doxorubicin is administered at the dose of 50 mg/m 2 on days 1, 22 and 57 of the induction phase. According to our modification doxorubicin was administered on days 1, 15, 29, 43 and 57 of the induction phase. Complete remission of malignancy was achieved in 20 patients (67%). Partial remission was achieved in 3 patients (10%). In total, objective remission (CR + PR) was achieved in 23, i.e. 77% of treated patients, 37% survived 2 years and 33% survived 5 years. The most common adverse events observed during therapy were haematological complications: anaemia, granulocytopenia and thrombocytopenia. They were the cause of one treatment-related death (neutropenic fever). Hyperglycaemia was observed due to use of high doses of steroids in the chemotherapy regimens under consideration. Increased intensity of anthracycline administration in our modification of Coleman’s regimen was not associated with increased frequency of cardiological complications; however, the total dose did not exceed the acceptable cumulative dose of this medication.